IMPLEMENTATION OF RADIO STATION COMMUNICATION STRATEGIES WITH COMBINING NEW MEDIA INTERNET (Case Study at PT. Radio Tjandra Buana Suara FM Cianjur) - Pupu Jamilah (Jurnal Multidisiplin Sahombu, 2023)
This research aims to determine the process of implementing strategies in dealing with media convergence .Tjandra FM Radio developed from initially being limited to conventional radio but then developed by combining it with new media such as the internet . The theoretical basis used is New media from Pierre Levy. This research uses a qualitative research method with a case study approach. In its implementation, Radio Tjandra no longer only broadcasts on air on radio but also utilizes internet media as a process of expanding listeners, increasing existence and also broadcasting advertisements. What is done is by creating a social media account. such as Facebook, Twitter, Instagram, creating websites and streaming radio applications. Apart from that, Radio Tjandra also carries out many off air or on air activities in busy places using an OB Van. The results of the implementation process of the strategy of combining radio with the internet have not yet produced maximum results for expanding advertising, however for expanding listening it has provided significant results as proven by increasing the number of listeners every day.So the future challenge for Radio Tjandra FM is how to find new, more interesting innovations, and also develop existing human resources so that the initial vision and mission can be achieved and the radio's existence increase